De V.O.C. op zoek naar de Goud- en zilvereilanden: de waar gebeurde avonturen van het schip de Breskens in het jaar 1643 in Japan - Vonk, P. G. (Utrecht Vos Holland, 1997)
In the Golden Age, the V.O.C. ship 'de Breskens' made a spectacular voyage of discovery, but it ended up in Japan after a violent storm. This had major consequences for the crew, the ship itself and for the unique relationship between Japan and the Netherlands. The story seems too wonderful to be true, but it really is.
Keywords: Vereenigde Oostindische Compagnie; 17th Century (1601-1700); History; Maritime transport; Netherlands; Japan